Can Organic Amendments Support Sustainable Vegetable Production?. (1st September 2017) - de Rosa, Daniele; Basso, Bruno; Rowlings, David W.; Scheer, Clemens; Biala, Johannes; Grace, Peter R.
Abstract : Core Ideas: Accounting for the N release from organic amendments improves N use efficiency and promotes soil C storage in horticultural soils. Regional N fertilizer recommendations are affected by a high degree of uncertainty. Crop simulation model can help to develop efficient site‐specific N management. Application rates of synthetic fertilizer to agricultural fields can be reduced through better understanding of N supplied by organic amendments (OA). Field and simulation experiments were performed to quantify the effect of N released from OA application on crop production and selected soil properties in an intensively managed vegetable crop rotation. The SALUS crop model was used to simulate yield, soil N, and soil organic carbon (SOC) dynamics under different combinations of composted or raw OA and synthetic N fertilizer application rates. SALUS accurately simulated aboveground crop biomass production ( r 2 = 0.91, RMSE = 1.7 t ha −1 ) and crop N uptake ( r 2 = 0.96, RMSE = 15 kg N ha −1 ) under different N management strategies as well as SOC level ( r 2 = 0.51, RMSE = 1 t C ha −1 ) and soil mineral N ( r 2 = 0.58, RMSE = 56 kg N ha −1 ). No difference in crop biomass production was found with N fertilizer reductions up to 27% of the conventional N fertilizer rate when combined with OA application. A 12‐yr scenario analysis using SALUS indicated that conventional N fertilizer can be further reduced by up to 50% while sustaining crop biomass production, thereby potentially reducing N losses to the environment. Data gathered from the field study and simulation scenarios highlighted the positive effect of composted OA to maintain soil C levels. This contrasts with average annual SOC losses of 3.7% observed in long‐term simulation scenarios in systems with only N fertilizer or raw OA applications.